A quantified approach to assessing the effectiveness of nuclear reactor pressure vessel neutron fluence monitoring programs - Kulesza Joel; Fischer Greg (EPJ Web of Conferences)
This paper presents a quantitative approach to characterize the effectiveness of neutron fluence monitoring programs using adjoint neutron transport calculations. The results of adjoint calculations are useful for this purpose because the adjoint solution is the expected contribution from one region of phase space to a response of interest, i.e., the importance of that region of phase space to the response. Thus, by identifying a response of interest (for this work, the fast (E > 1.0 MeV) neutron fluence rate at the peak fluence rate location in the reactor pressure vessel (RPV)), one can identify the fuel regions most important to that response. Once identified, the ability of various surveillance programs to adequately monitor the most-important fuel region(s) can be assessed. The approach described is applied to a three-loop Westinghouse pressurized water reactor to compare the effectiveness of surveillance-capsule neutron dosimetry versus ex-vessel neutron dosimetry to monitor the fuel assemblies that contribute to the peak fast (E > 1.0 MeV) neutron fluence rate in the RPV.